Nitroglycerin Use in Myocardial Infarction Patients: Risks and Benefits - Ferreira, Julio C.B. (2011)
Acute myocardial infarction and its sequelae are leading causes of morbidity and mortality worldwide. Nitroglycerin remains a first-line treatment for angina pectoris and acute myocardial infarction. Nitroglycerin achieves its benefit by giving rise to nitric oxide, which causes vasodilation and increases blood flow to the myocardium. However, continuous delivery of nitroglycerin results in tolerance, limiting the use of this drug. Nitroglycerin tolerance is due, at least in part, to inactivation of aldehyde dehydrogenase 2 (ALDH2), an enzyme that converts nitroglycerin to the vasodilator, nitric oxide. We have recently found that, in addition to nitroglycerin’s effect on the vasculature, sustained treatment with nitroglycerin negatively affects cardiomyocyte viability following ischemia, thus resulting in increased infarct size in a myocardial infarction model in animals. Co-administration of Alda-1, an activator of ALDH2, with nitroglycerin improves metabolism of reactive aldehyde adducts and prevents the nitroglycerin-induced increase in cardiac dysfunction following myocardial infarction. In this review, we describe the molecular mechanisms associated with the benefits and risks of nitroglycerin administration in myocardial infarction. (167 of 200).